Aural rehabilitation of people with disabilities - Oyiborhoro, John M. A. (Elsevier Academic Press, 2005)
This book provides a comprehensive audiological assessment and management of people with disabilities.
Keywords: Hard of hearing people -- Rehabilitation.; People with disabilities -- Rehabilitation.; Audiology.; Correction of Hearing Impairment; Persons with Disabilities -- rehabilitation.; Audiology; Audiologie.; HEALTH & FITNESS -- Hearing & Speech.; MEDICAL -- Audiology & Speech Pathology.; Rehabilitation of Hearing Impaired.; Disabled Persons -- rehabilitation.; Hearing impaired -- Rehabilitation.; Hearing impaired -- Rehabilitation; People with disabilities -- Rehabilitation; Percepção auditiva (reabilitação)